Collaborative narrative writing: A digital photography task in an Indonesian Islamic secondary school - Ferdiansyah, Sandi (Indonesian Journal of Applied Linguistics, 2018)
Despite being widely used in writing classrooms, collaborative writing along with a digital photography task in a secondary school context receives scanty attention. To fill this gap, the present case study attempts to showcase the design and implementation of a digital photography task in collaborative writing. It looks at (1) a group negotiation process of selecting story ideas and joint story drafting and (2) collaborative meaning-making processes in story writing and creativity building through visually-mediated narrative writing. Seven groups of third-year students of 16–17 years old participated in this study. They were engaged in a collaborative project to create digital stories. The findings of the study showed that a collaborative process in narrative writing through digital photography assisted the students to get involved actively in selecting digital software and jointly generating ideas of the story. The study also exemplifies the potential use of digital photography in helping the students develop ideas and enhance their narrative writing quality. The pedagogical implication of the study is that framing a visually- and technologically-based collaborative narrative writing task encourages students’ engagement in writing processes and empowers them to become engaged storytellers.